2015
DOI: 10.1002/cmdc.201500395
|View full text |Cite
|
Sign up to set email alerts
|

A Double Whammy: Targeting Both Fatty Acid Amide Hydrolase (FAAH) and Cyclooxygenase (COX) To Treat Pain and Inflammation

Abstract: Pain states that arise from non-resolving inflammation, such as inflammatory bowel disease or arthritis, pose an unusually difficult challenge for therapy because of the complexity and heterogeneity of their underlying mechanisms. It has been suggested that key nodes linking interactive pathogenic pathways of non-resolving inflammation might offer novel targets for the treatment of inflammatory pain. Non-steroidal anti-inflammatory drugs (NSAIDs), which inhibit the cyclooxygenase (COX)-mediated production of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 132 publications
1
12
0
Order By: Relevance
“…13 However, there is growing interest towards dual molecules such as FAAH/TRPV1 blockers and also FAAH/COX-2 inhibitors; 14 specifically, it is shown how COX-2-mediated transformation of anandamide into pro-algesic prostamides has led to the hypothesis of the presence of deeper functional connections between the endocannabinoid and prostanoid systems. 15 The interest in COX-2 inhibition has been emphasized by the fact that it is often involved in oxidative stress 16 and also in cancer progression. In fact, studies have demonstrated how prediagnostic use of NSAIDs, such as aspirin, and selective COX-2 inhibitors was, however, associated with a reduced rate of breast cancer recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…13 However, there is growing interest towards dual molecules such as FAAH/TRPV1 blockers and also FAAH/COX-2 inhibitors; 14 specifically, it is shown how COX-2-mediated transformation of anandamide into pro-algesic prostamides has led to the hypothesis of the presence of deeper functional connections between the endocannabinoid and prostanoid systems. 15 The interest in COX-2 inhibition has been emphasized by the fact that it is often involved in oxidative stress 16 and also in cancer progression. In fact, studies have demonstrated how prediagnostic use of NSAIDs, such as aspirin, and selective COX-2 inhibitors was, however, associated with a reduced rate of breast cancer recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Several of these lignans displayed significant cyclooxygenase (COX) and lipoxygenase (LOX) inhibiting activity [16]. Other COX inhibitors have also been found to influence endocannabinoid catabolism [17]. Therefore, we focused on lignans from noni fruit in our assays, including morindolin, isoprincepin, 3,3'-bisdemethylpinoresinol, americanin A, americanoic acid A.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it is not surprising that targeting the endocannabinoid system is suggested as a promising treatment opportunity for a number of pathological states. To mention just a few recent reviews, related to the nervous system only, these include anxiety and depressive symptoms [ 33 , 34 ]; Alzheimer's disease [ 35 ]; schizophrenia [ 36 - 38 ]; pain and inflammation [ 9 , 39 , 40 ]; multiple sclerosis [ 41 ]; stroke and brain trauma [ 42 ]; Parkinson's disease [ 43 ]; epilepsy [ 44 ] and addiction [ 45 ].…”
Section: The Endocanabinoid Systemmentioning
confidence: 99%
“…By engaging the native protective cell signalling pathways, endocannabinoids (eCBs) as well as related phytocannabinoids can be promising candidates for the treatment of chronic pain since they possess low toxicity and low addiction potential. In this regard, inhibitors of enzymes (for example, fatty acid amide hydrolase (FAAH)) that hydrolyze eCBs are of particular interest [ 9 ].…”
Section: Introductionmentioning
confidence: 99%